Peran Hukum Adat dalam Pelestarian Tradisi Suku Baduy di Banten - Purwanti (Rampai Jurnal Hukum (RJH), 2025)
This study examines the vital role of the customary law of the Baduy Tribe in efforts to preserve their traditions and natural order. The Baduy customary law is deeply rooted in the Sunda Wiwitan belief and the principle of "pikukuh karuhun," which emphasizes harmony with nature and maintaining ecological balance. This principle is reflected in nature conservation practices, such as protecting forests and refraining from damaging valleys, as well as in regulating social and economic life that prioritizes simplicity and honesty. Despite facing the challenges of modernization, the Baduy community continues to strive to sustain their customary law by internalizing traditional values to safeguard cultural identity and environmental preservation. The research questions are 1) What are the structure, values, and role of the Baduy Tribe’s customary law? 2) How is the synergy between the indigenous community and the government in preserving traditions? Using qualitative methods to gain a deep and comprehensive understanding of the role and participation in this phenomenon, with a case study on the Baduy community in Banten, the study finds that 1) The core values of Baduy customary law are simplicity, honesty, mutual cooperation (gotong royong), and harmony with nature, serving as a system for cultural control. 2) The government plays a very important and strategic role in supporting the preservation of the Baduy community’s customary laws and traditions. Holding regulatory and administrative authority, the government can formulate policies that support indigenous communities and protect cultural existence from external threats.   Abstrak Penelitian ini mengkaji peran vital hukum adat Suku Baduy dalam upaya pelestarian tradisi dan tatanan alam mereka. Hukum adat Baduy berakar kuat pada kepercayaan Sunda Wiwitan dan prinsip "pikukuh karuhun," yang menekankan keselarasan dengan alam dan menjaga keseimbangan ekologi. Prinsip ini diwujudkan dalam konservasi alam, seperti menjaga hutan dan tidak merusak lembah, serta dalam pengaturan kehidupan sosial dan ekonomi yang mengutamakan kesederhanaan dan kejujuran. Meskipun menghadapi tantangan modernisasi, masyarakat Baduy terus berupaya mempertahankan keberlangsungan hukum adat mereka dengan menginternalisasi nilai-nilai tradisional untuk menjaga identitas budaya dan pelestarian lingkungan. Lalu 1) Seperti apa struktur, nilai-nilai, serta peran hukum adat Suku Baduy 2) Sinergi antara Masyarakat adat dan pemerintah dalam pelestarian tradisi dengan menggunakan metode kualitatif yaitu untuk mendapatkan pemahman yang mendalam dan komprehensif mengenai fenomena peran serta dengan studi kasus pada Masyarakat di suku Baduy Banten lalu menghasilkan 1) Nilai utama hukum adat Baduy adalah kesederhanaan, kejujuran, gotong royong, dan harmoni dengan alam serta sebagai sistem pengendali budaya 2) Pemerintah memiliki peran yang sangat penting dan strategis dalam membantu pelestarian hukum adat dan tradisi masyarakat Suku Baduy memiliki kekuasaan regulatif dan administratif, pemerintah dapat menciptakan kebijakan yang berpihak pada masyarakat adat serta melindungi eksistensi budaya dari ancaman eksternal